The Effectiveness of Community-Based Cardiac Rehabilitation Programs in Reducing The Relapse Rate of Post-Myocardial Infarction Patients - Sisca, Meike (Action Research Literate, 2024)
Cardiovascular diseases, particularly myocardial infarction (MI), are a leading cause of morbidity and mortality worldwide. Post-MI patients are at high risk for recurrent ischemic events. While traditional hospital-based cardiac rehabilitation (CR) has long been the standard, Community-Based Cardiac Rehabilitation (CBCR) programs have emerged as an accessible alternative. This literature review evaluates the effectiveness of CBCR in reducing relapse rates among post-MI patients. A systematic literature review was conducted in August 2024 using databases such as Scopus, PubMed, Google Scholar, and Crossref. Relevant articles published between 2014 and 2024 in English were selected based on predefined inclusion criteria. The PICO framework guided the study, focusing on the effectiveness of CBCR compared to traditional CR. Nineteen articles were included in the review after a rigorous selection process. The review found that CBCR programs significantly improved patient adherence, reduced relapse rates, and enhanced cardiovascular health. Compared to hospital-based programs, CBCRs were more accessible, particularly in underserved areas, and fostered greater patient engagement. Moreover, CBCR participants showed improvements in medication adherence, physical activity, and psychological well-being, with many studies reporting lower rates of rehospitalization. CBCR programs are an effective alternative to hospital-based CR, offering comparable or superior outcomes in reducing relapse rates and improving overall health. Their accessibility and patient-centered approach make them a viable option for post-MI care, particularly in regions with limited healthcare access. Further research is recommended to explore the long-term benefits of CBCR on patient outcomes.